CREATION OF COMIC STRIPS USING CANVA IN TEACHING WRITING TO STUDENTS - Fitria, Tira Nur (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2023)
This study simulates the making of comic strips using Canva in teaching writing skills. This research utilizes descriptive qualitative. The analysis shows that creating comic strips using Canva is easy and simple. Open Canva at www.canva.com/ on mobile/ desktop then sign in or register using email, Facebook, or Google. Search for "comics" to start designs. Browse templates, start with a blank page, or choose Canva's ready-made templates. Experiment with features comic designs then customize comics with color schemes, lawyers, font styles, and combinations of stickers, icons, and illustrations. Rearrange speech bubbles and frames, upload images, save/publish and share. Teachers can use Canva to create/design comic strips for writing English sentences/conversations. We can use the available comic strip template patterns or customize them as needed. For example, we create/design a comic strip about "My Daily Activity", we ask students to write sentences/essays of descriptive text according to the picture instructions in the comic strips from the activities of waking up to going to school using the present tense. We can ask students to write sentences/essays about "All About Me". We can ask students to write down what is depicted in the comic strips, for example, personal information including name, birthday, address, family, favorite, hobby, or ambition. Several ways need to be considered in creating comic strips such as the concept/story idea, storyline, and attractive image. For making interesting and educative learning comics, we can include an element of humor, insert material in character conversations, use casual language, and create attractive visuals.